DOZ047.115: Quality and readability of esophageal atresia information on the Internet. (24th June 2019) - O'Connor, B R; Doherty, E; Friedmacher, F; Vernon, L; Paran, T S
Abstract: Introduction: Increasingly in pediatric surgical practice, patients, their parents, and surgeons alike use the Internet as an easily and quickly accessible source of information about conditions and their treatment. The quality and reliability of this information may often be unregulated. We aim to objectively assess the online information available relating to esophageal atresia and its management. Methods: We performed searches for 'oesophageal atresia' and 'esophageal atresia' using the Google, Yahoo, and Bing engines to encompass both European and American spellings. We assessed the first 20 results of each search and excluded duplicates or unrelated pages. The DISCERN score and the Health on the Net Foundation Code (HONcode) toolbar were utilized to assess the quality of information on each website. We evaluated readability with the Flesch reading ease (FRE) and the Flesch–Kincaid grade (FKG). Results: Of the original 120 hits, 61 were excluded (51 duplicates, 10 unrelated). Out of 59 individual sites reviewed, only 13 sites were HONcode approved. The mean overall DISCERN score was 52.55 (range: 22–78). The mean DISCERN score for the search term 'oesphageal atresia' was 57 (range: 22–78) in comparison to 59.03 for 'esophageal atresia' (range: 27–78). Google search had the lowest overall mean DISCERN score at 54.83 (range: 35–78), followed by Yahoo at 58.03 (range: 22–78), and Bing with the highest overall mean score of 61.2 (range: 27–78). The majority of websites were graded excellent (≥63) or good (51–62), 43% and 27%, respectively; 20% were scored as fair (39–50), with 10% being either poor (27–38) or very poor (≤26). In terms of readability, the overall Flesch Reading Ease score was 33.02, and the overall Flesch–Kincaid grade level was 10.3. Conclusions: The quality of freely available online information relating to esophageal atresia is generally good but may not be accessible to everyone due to being relatively difficult to read. We should direct parents towards comprehensive, high-quality, and easily readable information sources should they wish to supplement their knowledge about esophageal atresia and its management.